Case Report: Neo-ostium creation with saphenous vein in a patient with anomalous origin of the right coronary artery - Bahar Temur; Zeynep Sıla Özcan; Serdar Başgöze; Selim Aydın; Füsun Güzelmeriç; Ersin Erek (Frontiers Media S.A., 2023)
Anomalous origin of the right coronary artery from the left sinus of Valsalva is a rare congenital anomaly. Most patients may be asymptomatic, but some may experience major cardiac events such as syncope, arrhythmias, and sudden cardiac death. We present a 16-year-old patient, who had several syncopes, with anomalous origin of the right coronary artery from the left coronary sinus, with an intramural and interarterial course between the pulmonary artery and the aorta. We describe a new surgical procedure of neo-ostium creation with a saphenous vein.